Foreword: Is Justice Just Us? - Slobogin, Christopher (2000)
This is a review of JUSTICE, LIABILITY AND BLAME, by Paul Robinson and John Darley. The book is a summary of 18 studies which surveyed lay subjects about their attitudes toward various aspects of criminal law doctrine, including the act requirement for attempt, omission liability, accomplice liability, the felony-murder role, and the intoxication and insanity defenses. In virtually every study, the authors found that the subjects disagreed with the Model Penal Code's position, the common law's position, or both. The authors contend that results of surveys such as theirs should play a significant role in designing criminal doctrine, both because lay opinion can inform the normative judgments inherent therein and because gaps between the law and the public's views can exacerbate noncompliance with the law. This review argues that neither reason supports giving significant weight to such surveys. It also quibbles with minor aspects of the authors' methodology. The overall conclusion, however, is that the book generates numerous interesting hypotheses for criminal theoreticians and teaches useful lessons to all those who would do social science in the service of the law